A SYSTEMATIC EVALUATION OF RYFF'S PSYCHOLOGICAL WELL-BEING SCALE AND THE IMPLICATIONS FOR CROSS-CULTURAL VALIDITY AS WELL AS SPIRITUAL VALUES - Aditya Aryo Nur Kusumo (Faculty of Psychology, Diponegoro University, 2025)
This research aimed to discuss Ryff's psychological well-being (PWB) scale and looked at problems with making it valid and reliable for different cultures and groups. It also explains how Ryff's PWB scale has changed over time and gave ideas for what to do in future publications. The method used was a Systematic Literature Review (SLR), where articles were found, examined, and studied critically. Among 429 articles, only 29 met the criteria and were used for further checking. The results showed that the original 120-item scale was valid and reliable, but it was too long to use easily. A shorter version with 18 items did not have good enough validity. Some studies also said the six-factor model in Ryff's scale did not match the data, and new models were suggested instead. This research confirmed there was a need to check the examination across more cultures, make better items, and think about new theories. It also said the six-factor model could work well with Islamic values added to it.